2011
DOI: 10.1097/rct.0b013e3182372a12
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Logistic Model for T2* Dynamic Susceptibility Contrast Magnetic Resonance Imaging (dscMRI) Perfusion Studies

Abstract: There are a number of T1- and T2-based dynamic contrast-enhanced magnetic resonance imaging pharmacokinetic modeling approaches to study cancer microvasculature. Alternatively, model-free approaches offer an easy, quantitative assessment of microcirculation. In this work, we investigate a 6-parameter model-free approach applied to a T2*-weighted echo-planar imaging bolus response curve. We tested this new approach on a small cohort of patients with clinically diagnosed primary rectal carcinoma before adjuvant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…8 Dynamic susceptibility contrast (DSC) MRI is most commonly used to measure perfusion in the brain. 9 However, studies have also shown the feasibility of using this approach to assess microvasculature in rectal cancer 10 and phenotypic characteristics of breast tumors. [11][12][13] Recognizing that rectal tumors are highly angiogenic, it is hypothesized that DSC-MRI may provide valuable information for assessing pathophysiological properties in this patient group.…”
mentioning
confidence: 99%
“…8 Dynamic susceptibility contrast (DSC) MRI is most commonly used to measure perfusion in the brain. 9 However, studies have also shown the feasibility of using this approach to assess microvasculature in rectal cancer 10 and phenotypic characteristics of breast tumors. [11][12][13] Recognizing that rectal tumors are highly angiogenic, it is hypothesized that DSC-MRI may provide valuable information for assessing pathophysiological properties in this patient group.…”
mentioning
confidence: 99%